Evaluating the impact of tilt angles and tracking mechanisms on photovoltaic modules in Ethiopia - Assaye Gedifew; Amare Benor (Frontiers in Energy Research)
This study investigated the influence of site location, tilt angle, and solar orientation on Ethiopia’s photovoltaic (PV) module performance. We determined optimal tilt angles for different time scales and locations across the country by analyzing global horizontal radiation data and employing various decomposition and transposition models. Results showed that optimal tilt angles increase with latitude, ranging from 0° to 47.9° monthly and from 14.1° to 21.5° annually. Seasonal optimal tilt angles were found to be 29.2°, 21.65°, 12.34°, and 8.8° for winter, autumn, spring, and summer, respectively. Additionally, the study compared the performance of PV modules with different tracking mechanisms. Dual/full-axis tracking yielded the highest energy gain (44.89%), while NS tracking resulted in a significant loss (28.46%). This research provides valuable insights for optimizing Ethiopia’s PV system design and installation, aiding in accurate energy assessment and forecasting.